PERANAN AUDIT INTERNAL, KOMITE AUDIT, DAN SISTEM PENGENDALIAN INTERNAL DALAM PENCEGAHAN FRAUD - Linda Karlina (2022)
This study is a quantitative study that aims to determine the effect of the role of internal audit, audit committee, and internal control system in preventing fraud. This study uses food and beverage sub-sector manufacturing companies in 2018-2020 as a sample. The sample selection used purposive sampling technique and obtained 15 companies as samples with as many as 45 units of data analysis. Hypothesis testing in this study used Multiple Linear Regression Analysis with SPSS version 25 program and a significance level of 5% (0.05). The results of the test show that (1) the role of internal audit has no significant effect on fraud prevention, (2) the role of the audit committee has no significant effect on fraud prevention, (3) the role of the internal control system has no significant effect on fraud prevention. Keywords : Internal Audit, Audit Committee, Internal Control System, and Fraud Prevention